Laser-scribed Ru organometallic complex for the preparation of RuO2 micro-supercapacitor electrodes on flexible substrate. (10th August 2018) - Brousse, K.; Nguyen, S.; Gillet, A.; Pinaud, S.; Tan, R.; Meffre, A.; Soulantica, K.; Chaudret, B.; Taberna, P.L.; Respaud, M.; Simon, P.
Abstract: Flexible and miniaturized energy storage devices are necessary for the development of wearable applications. Hence, micro-supercapacitors, which offer good compromise between energy densities, high power capabilities and long cycle life, have to be integrated on flexible substrates. Laser-writing techniques are suitable for engineering multiple materials within short times. The integration of RuO2 onto flexible substrates usually relies on the irradiation of ruthenium salts displaying an oxidation state of the metal varying from +II to +IV, and for which additives are necessary in the electrode to compensate the lack of adherence of the resulting large ruthenium grains. Here, we report a facile and scalable preparation of RuO2 flexible electrodes from direct laser-writing of a spin-coated solution of ruthenium molecular precursor, the Ru(COD)(COT) (COD = 1, 5-cyclooctadiene, COT = 1, 3, 5-cyclooctatriene) and cellulose acetate, without the addition of any other capacitive material in the electrode. The obtained Ru/RuO2 deposit showed good adherence on a Au thin film deposited on either silicon or polyimide (Kapton™) substrates, and delivered up to 16 mF cm -2 at 100 mV s −1 in 1 M H2 SO4 . Furthermore, the flexible electrodes exhibited good capacitance retention, with more than 60% of the initial capacitance recorded at high scan rate of 10 V s −1 . Laser-writing using this original ruthenium metallic precursor offers an easy and scalable fabrication method for preparing additive-free RuO2 -based micro-supercapacitor electrodes. Graphical abstract: Image 1 Highlights: Flexible RuO2 micro-supercapacitor electrodes were prepared from laser-writing. Molecular Ru(COD) (COT) complex was used as metallic ruthenium precursor. Thin film RuO2 adheres on polyimide/Ti/Au without additional capacitive material. Laser-scribed RuO2 delivers up to 16 mF cm −2 with high power capabilities in H2 SO4 .